2021
DOI: 10.1021/acs.jafc.1c00365
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Lanthanum and Calcium on Cadmium Accumulation in Wheat with Special Reference to TaNramp5 Expression Regulated by Calmodulin

Abstract: Lanthanum (La), calcium (Ca), and cadmium (Cd) have similar physical and chemical properties because of their similar ionic radius. Although the interactions between La, Ca, and Cd have been frequently reported in plants, few studies have investigated the interactive effects of La and Ca on the growth and Cd accumulation in plants. Therefore, we investigated the interactive effects of La and Ca on the growth and Cd accumulation in wheat under Cd exposure by a hydroponic experiment. The results indicated that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…42 Yang et al (2021) reported that La could share the same binding site in calmodulin with Ca and thereby reduce the accumulation of Cd in wheat. 16 Moreover, calmodulin and calmodulin-like proteins are important regulators against plant disease and after binding Ca 2+ ; they regulate the expression of pathogenesis-related genes and improve plant resistance. 43 Hence, we hypothesized that La 2 O 3 NMs could interact with calmodulin, thereby regulating plant defense.…”
Section: Effect Of La 2 O 3 Nms On the Activity Of Antioxidative Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…42 Yang et al (2021) reported that La could share the same binding site in calmodulin with Ca and thereby reduce the accumulation of Cd in wheat. 16 Moreover, calmodulin and calmodulin-like proteins are important regulators against plant disease and after binding Ca 2+ ; they regulate the expression of pathogenesis-related genes and improve plant resistance. 43 Hence, we hypothesized that La 2 O 3 NMs could interact with calmodulin, thereby regulating plant defense.…”
Section: Effect Of La 2 O 3 Nms On the Activity Of Antioxidative Enzymesmentioning
confidence: 99%
“…15 More importantly, La has a higher binding affinity to protein than Ca due to its stronger electropositivity. 16 Therefore, we hypothesized that La 2 O 3 NMs could sustainably supplement La ions in plants to activate CaM functions, subsequently increasing SA content and promoting SAR. Additionally, research has demonstrated that the bioavailability of NMs is closely related to its surface properties (e.g., hydrophobicity and surface charge) and size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rare earth elements have been used as agricultural amendments to promote plant growth and suppress disease occurrence. [10][11][12] After amendment with rare earth elements, more than 100 crops exhibited 5-15% increases in production over untreated controls. 13 Lanthanum (La), one of the most commonly used rare earth elements, has similar properties to calcium (Ca) due to its similar ionic radius (1.06 Å) to that of Ca (0.99 Å).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Importantly, La has a stronger binding affinity to CAM than Ca due to its greater electropositivity. 11 Wang et al (2016) reported that foliar application with low concentration (30 μM) La ions could enhance the CAM levels and function in Arabidopsis leaves, while higher concentrations (80 μM) inhibited the activity due to disrupted protein structure. 18 NMs have been shown to sustainably deliver nutrients or active compounds for plant growth or to effectively convey resistance due to their high bioavailability and tunable-release profiles.…”
Section: Introductionmentioning
confidence: 99%